Development and evaluation of a checklist to support decision making in cancer multidisciplinary team meetings: MDT-QuIC. - Lamb, B; Sevdalis, N; Sevdalis, N; Vincent, C; Vincent, C; Green, J; Green, J (2012)
BACKGROUND: The quality of decision-making in cancer multidisciplinary team (MDT) meetings is variable, which can result in suboptimal clinical decision making. We developed MDT-QuIC, an evidence-based tool to support clinical decision making by MDTs, which was evaluated by key users. METHODS: Following a literature review, factors important for high-quality clinical decision making were listed and then converted into a preliminary checklist by clinical and safety experts. Attitudes of MDT members toward the tool were evaluated via an online survey, before adjustments were made giving rise to a final version: MDT-QuIC. RESULTS: The checklist was evaluated by 175 MDT members (surgeons = 38, oncologists = 40, specialist nurses = 62, and MDT coordinators = 35). Attitudes toward the checklist were generally positive (P < 0.001, 1-sample t test), although nurses were more positive than other groups regarding whether the checklist would improve their contribution in MDT meetings (P < 0.001, Mann-Whitney U test). Participants thought that the checklist could be used to prepare cases for MDT meetings, to structure and guide case discussions, or as a record of MDT discussion. Regarding who could use the checklist, 70% thought it should be used by the MDT chair, 54% by the MDT coordinator, and 38% thought all MDT members should use it. CONCLUSION: We have developed and validated an evidence-based tool to support the quality of MDT decision making. MDT members were positive about the checklist and felt it may help to structure discussion, improve inclusivity, and patient centeredness. Further research is needed to assess its effect on patient care and outcomes.